PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. ANUGRAH ARGON MEDICA PALEMBANG - Kholilah, Kholilah; Gergita, Aldhera; Puspasari, Mardiana; Kohar, Zawawi (Universitas Muhammadiyah Palembang, 2021)
Purpose –The purpose of this study was to determine the effects of work environment and work discipline on employee performance of PT. Anugrah Argon Medica Palembang. Design/methodology –This type of research in this study was associative. The population in this study was the number of PT.Anugrah Argon Medica Palembang, amounting to 120 employees and sample staken as many as 54 respondents with the sampling technique Proportionate Sampling. The analytical method used qualitative quantitative. The data analysis technique in this research was multiple linear regression, F test, t test, coefficient of determination .Findings - The results of multiple linear regression analysis showed that there was a positive effect on environmental variables and work discipline on employee performance of PT.Anugrah Argon Medica Palembang. The results of F hypothesis test together showed that there was a significant effect of work environment and work discipline on employee performance.The resultsoft hypothesis test individually showed that there was a significant effect of work environment on employee performance.The results of hypothesis test also showed that there was a significant effect of work discipline on empl oyee performance. The results of the coefficient of determination on work environment and work discipline were only able to contribute to changes that occurred in employee performance by 44.3%.